POSSIBLE RAPID METHOD FOR THE DETERMINATION OF CONCRETE’S FROST RESISTANCE - Nikolskiy, Sergey; Vatin, Nikolay; Pertseva, Olga (Journal of Applied Engineering Science, 2015)
During this research, the theoretical analysis of dependence concrete’s frost resistance of sample and energy, which is emitted by a sample at destruction, was carried out. The offered method includes measurement of residual deformation of a sample after the one cycle of freezing defrosting, measurement of long strength and measurement of short-term strength. Frost resistance of a sample is as the mathematical relation of these energies, and the frost resistance of concrete is calculated as arithmetic mean on samples. The offered method doesn’t demand long tests, it’s high efficiency and wide scope, but special laboratory equipment is necessary.